Impacto del tratamiento de la NIC 2 en la liquidez de Comercial Jonma - Tamayo Riofrio, María Auxiliadora (2023)
The Comercial Jonma microenterprise was founded in June 2017, it is located to the Southwest of the city of Guayaquil, it is dedicated to the wholesale and retail sale of bicycle parts and accessories: tires, helmets, tubes, patches, etc. The purpose of the investigation is to analyze the impact of IAS 2 on the liquidity of Commercial Jonma, due to the fact that the commercial does not establish an adequate control of its inventories, which has caused a certain decrease in its ability to cover obligations. The main objective is to know the shortcomings that the commercial has with the management, control and/or treatment of the inventory through its commercial activities and how the company is directly affected by the ignorance of the IAS 2 regulations and by the scarcity of procedures that establish a good management; It is essential to keep a constant track of the available inventory, this implies the physical taking of the products in a certain time to compare the results with the records that the microenterprise contains regarding the entry and exit of the inventory and also helps to identify discrepancies, such as losses due to theft or registration errors. To obtain these results, research techniques were applied, which are: interviews and direct observation, the situation of the commercial was widely known.